Experiência de um ano de modelo de programa de prevenção contínua do melanoma na cidade de jaú-sp, brasil - Salvio, Ana Gabriela [UNESP]; Assumpção Jr., Ary; Segalla, José Getúlio Martins [UNESP]; Panfilo, Beatriz Lhanos; Nicolini, Helen Renata; Didone, Reniele (FapUNIFESP (SciELO), 2011)
BACKGROUND: Worldwide incidence of melano ma has increased in recent years faster than any other cancer. Although it represents only 4% of skin cancers it is never the less responsible for 60% of skin cancer deaths. This makesmelanoma a public health problem. OBJECTIVES: The aim of this study was the development of a continuous pro gram for melanoma prevention and early detection. METHODS: A city of around 130,000 inhabitants in the state of São Paulo, Brazil, was chosen for the development of a pilot project covering primaryprevention and early diagnosis of melanoma. A nursing team worked for approximately 30 days in each of the 13 health centers in the city of Jaú (SP), providing guidance on self-exami nation of the skin, photo protection and recognition of early signs of melanoma. Patients with suspicious lesions were immediately sent to the reference hospital for medical and dermoscopicscreening. Excisionalbiopsies were performed on suspected melanomas. RESULTS: 4 four cases of early stage mela no ma and 3 dysplastic nevi were diagnosed. Of the people inter vie wed, 74% worked either part-time or full-time exposed to sun and over 60% claimed to never use sunscreen. CONCLUSION: This is a new and effective model formela no ma pre vention and early diagnosis. In short, the mela - noma prevention pro gram is able to quickly identify suspicious lesions, lea ding to early diag no sis and bet terchances of survival. © 2011 by Anais Brasileiros de Dermatologia.
One year experience of a model for melanoma continuous prevention in the city of Jaú (São Paulo), Brazil
Keywords: Disease prevention; Early diagnosis; Melanoma